Damage compensation for innocent defendants and Convicts in Iran and the Canadian legal system - Khanjani, Mohammad Kazem; Bahadori, Atoosa (Technium Social Sciences Journal, 2021)
In the field of innocent defendants and convicts' damage compensation who have endured further losses due to issue criminal supply contracts or orders execution, their innocence has been cleared by issuing acquittance sentences. It counted as one of the most challenging issues in private and criminal law. In these recent years, based on positive changes in the rules of Iran, a lot of works done for innocent defendants and convicts' damage compensation have endured different and unfair punishments. But no integration or constructive work has been done for guiltless convicts' damage compensation who have endured some parts or all their punishments, and their innocence has been proved but not predicted. The reverse of this matter is true in the Canadian law system. Only a guilty convict who has tolerated some or all parts of unfair punishment deserves to receive damage compensation. This study attempted to research the subject's international binding rules, and many practical strategies for guiltless convicts' damage compensation will be considered in both systems by a comparative study.